2000
DOI: 10.1016/s0009-2614(00)01225-2
|View full text |Cite
|
Sign up to set email alerts
|

Is there a barrier for the C2v insertion reaction in O(1D)+H2? A test dynamics study based on two-valued energy-switching potential energy surfaces

Abstract: We have calculated cross-sections and rate constants for the title reaction by using the quasiclassical trajectory method and a recently reported two-valued energy-switching potential energy surface for the water molecule. By varying the amplitude and rate of decay of a local Gaussian term which controls the appearance of a barrier along the C 2v minimum energy pro®le, an attempt has been made to answer the title issue. A comparison of the calculated rate constants with the available experimental data suggests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…reaction, which takes place on the ground-state potential energy surface of water, is known to play a significant role in combustion and atmospheric chemistry [113,114]. Two of the dissociation pathways examined in this work, namely, the dissociation of a single O-H bond and the C 2v dissociation path of the water molecule into H 2 (X 1 Σ + g ) and O(2 p 4 1 D) are directly related to this important reaction.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…reaction, which takes place on the ground-state potential energy surface of water, is known to play a significant role in combustion and atmospheric chemistry [113,114]. Two of the dissociation pathways examined in this work, namely, the dissociation of a single O-H bond and the C 2v dissociation path of the water molecule into H 2 (X 1 Σ + g ) and O(2 p 4 1 D) are directly related to this important reaction.…”
Section: Methodsmentioning
confidence: 94%
“…In the case of another C 2v -symmetric cut, namely cut (iii), we followed the approximate energy path toward the dissociation of the water molecule into H 2 (X 1 Σ + g ) and O(2 p 4 1 D), determined using the potential function of Ref. [102] and defined by the coordinate Y , which is the distance between the O nucleus and the line connecting the H nuclei, and the properly optimized H-O-H angle α [113,114]. The equilibrium values of Y and α are Y e = 0.58641 Å and α e = 104.501 degree.…”
Section: Computational Detailsmentioning
confidence: 99%
“…OH þ H and its isotopic variants have been the subject of various experimental studies [1][2][3][4][5][6][7][8]. Numerous theoretical studies of its dynamics have also been carried out (for example, see [1,[5][6][7][9][10][11][12][13][14][15][16][17][18][19][20]) using the potential energy surfaces (PES) published for this system [9,[21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Varandas [28]; (---) SL1 PES [32]; (-· -·) SL3 PES [32]; (-) ES [21]; (-· · · -· · ·) ES-2v II [25]; (· · ·) ES-2v III [25] and (---) K PES [52]. et al [25] have shown that the reactivity on the ES-2v PES strongly depends on the shape of the small bump for the C 2v insertion. Adding a Gaussian term, they have been able to propose two modifications of this PES, namely ES-2v II and ES-2v III, with different reactivities as shown in this figure.…”
Section: Total Reactive Cross Sectionsmentioning
confidence: 99%
“…Numerous theoretical studies of its dynamics have also been carried out, for example see [11,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], using several potential energy surfaces (PESs) published for this system [29,[32][33][34][35][36][37][38][39][40][41][42][43]. These works have been the subject of partial reviews by Liu [44], Althorpe and Clary [45], Balucani et al [46] and Aoiz et al [47].…”
Section: Introductionmentioning
confidence: 99%